2001
DOI: 10.3310/hta5260
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of inhaler devices in asthma and chronic obstructive airways disease: a systematic review of the literature

Abstract: et al. Comparison of the effectiveness of inhaler devices in asthma and chronic obstructive airways disease: a systematic review of the literature. Health Technol Assess 2001;5(26). Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. Copies of the Executive Summaries are available from the NCCHTA website (see opposite). NHS R&D HTA Programme T he NHS R&D Health Technology Assessment (HTA) Programme was set up in 1993 to ensure that high-quality research information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
204
2
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(221 citation statements)
references
References 240 publications
(145 reference statements)
3
204
2
12
Order By: Relevance
“…This finding is in coherence with a systematic review of inhaler devices by Brocklebank et al which combined results from studies of more than one inhaler type, and found that maximum or "ideal" inhaler scores were attained by 59% of subjects with DPIs, 43% with MDI alone, and 55% with MDI plus holding chamber. 26 Most commonly performed error in the inhalation technique was in step number eight, ten and four by 100% of patients using pMDI and pMDI with spacer and 88% of the patients using DPI at baseline which decreased to 90%, 88% and 73% respectively at the same step after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in coherence with a systematic review of inhaler devices by Brocklebank et al which combined results from studies of more than one inhaler type, and found that maximum or "ideal" inhaler scores were attained by 59% of subjects with DPIs, 43% with MDI alone, and 55% with MDI plus holding chamber. 26 Most commonly performed error in the inhalation technique was in step number eight, ten and four by 100% of patients using pMDI and pMDI with spacer and 88% of the patients using DPI at baseline which decreased to 90%, 88% and 73% respectively at the same step after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of incorrect inhalation technique varies from 4 to 94%. 10,[24][25][26][27] There are many reasons behind incorrect inhalation technique. Patients may be confused with devices requiring different inhalation techniques or have difficulty using their aerosol devices correctly.…”
Section: Problems With Patient Education and Adherence To Aerosol Thementioning
confidence: 99%
“…anti-leukotrienes, LTRAs) in moderate asthma conclude that ICS produce better outcomes, though whether this is true for all patients with mild or intermittent asthma is debated. [56][57] Such trials do not address the practical issues that impact on effectiveness in real-life primary care practice such as inadequate inhalation technique, 58 perceived side effects of steroids, 59 patient preference for regular treatment, and the impact of adherence. 60 …”
Section: S5mentioning
confidence: 99%